2013
DOI: 10.1161/circulationaha.112.000699
|View full text |Cite
|
Sign up to set email alerts
|

Late Outcomes of Mitral Valve Repair for Mitral Regurgitation Due to Degenerative Disease

Abstract: Background-The pathological spectrum of degenerative diseases of the mitral valve (MV) that causes mitral regurgitation (MR) is broad, and there is limited information on late outcomes of MV repair in various subgroups of patients and pathologies. This study examines this issue. Methods and Results-All 840 patients who had MV repair for MR due to degenerative diseases from 1985 to 2004 were prospectively followed with clinical and echocardiographic evaluations at biennial intervals up to 26 years, median of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
215
3
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(241 citation statements)
references
References 35 publications
16
215
3
7
Order By: Relevance
“…Particularly when a prosthetic ring is used, a concomitant annuloplasty, besides remodeling the annulus and forcing leaflet coaptation, stabilizes the repair over time preventing annular redilatation and reducing the risk of late failure. The benefits of annuloplasty in valve repair have been confirmed by several authors [1][2][3][4] who found that the absence of annuloplasty was one of the most important risk factor for late failure of the repair. As far as the EE technique is concerned, in patients with degenerative MR, the long-term results of this procedure are excellent whenever an annuloplasty is concomitantly used.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Particularly when a prosthetic ring is used, a concomitant annuloplasty, besides remodeling the annulus and forcing leaflet coaptation, stabilizes the repair over time preventing annular redilatation and reducing the risk of late failure. The benefits of annuloplasty in valve repair have been confirmed by several authors [1][2][3][4] who found that the absence of annuloplasty was one of the most important risk factor for late failure of the repair. As far as the EE technique is concerned, in patients with degenerative MR, the long-term results of this procedure are excellent whenever an annuloplasty is concomitantly used.…”
Section: Discussionmentioning
confidence: 83%
“…Particularly when a prosthetic ring is used, repair durability is enhanced by increased leaflet coaptation and prevention of further dilatation of the mitral annulus. [1][2][3][4] After the introduction of the MitraClip system, however, MR has been treated in many patients by applying a percutaneous ringless edge-to-edge (EE) procedure. Defining the long-term results of the surgical EE repair performed without annuloplasty may help to foresee, at least partially, the possible late results of this percutaneous technique.…”
mentioning
confidence: 99%
“…6, 7 Multisurgeon practices have also reported comparable outcomes and demonstrated that recurrent MR after MV repair is associated with late death. 8 The aims of the present study were to investigate the consequences of recurrent MR after MV repair in patients with degenerative MR and to identify risk factors for recurrence.…”
mentioning
confidence: 97%
“…Hence, comprehensive dynamic physiological description of these poorly understood entities is now possible and may provide crucial pathophysiologic insights, offering stronger basis for recent efforts at mechanistic [12][13][14] and genetic [15][16][17] DMVD characterization. Furthermore, dynamic physiological characterization may provide insights crucial to surgical 18,19 or interventional 20 repair of each DMVD phenotype. Thus, our objective was, in patients in whom DMVD phenotype was defined by direct intraoperative visualization, to evaluate by quantitative 3D-transesophageal-echocardiography (3DTEE) combined with comprehensive quantitative MR and cardiac remodeling characterization, the static and dynamic characteristics of mitral annulus, leaflets, and prolapse in FED and DMD, throughout the cardiac cycle.…”
mentioning
confidence: 99%